2015
DOI: 10.1007/s10865-015-9679-5
|View full text |Cite|
|
Sign up to set email alerts
|

Neighborhood matters: the impact of Hispanic ethnic density on future depressive symptoms 1-year following an ACS event among Hispanic patients

Abstract: The Ethnic Density hypothesis posits that living around others from similar ethnic backgrounds reduces the risk of adverse mental health outcomes such as depression. Contrary to this hypothesis, previous work has shown that Hispanic ethnic density is cross-sectionally associated with increased depressive symptom severity among patients hospitalized with an acute coronary syndrome (ACS; myocardial infarction or unstable angina pectoris). To date, no study has examined the prospective association of Hispanic eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Additional studies have reported associations between higher Latino ethnic density and lower levels of depression overall 1718 or among only men, 89 and a curvilinear association between Latino ethnic density and depression, with those living in areas of moderate ethnic density having the most depressive symptoms. 19 In the only study to evaluate the association between residential segregation and mental health among Latinos, Lee 20 evaluated residential segregation as measured by the isolation index among 400 Latinos in the Midlife Development in the US (MIDUS) study in Chicago. Lee found that residential segregation was associated with a greater number of depressive and anxiety symptoms among both Mexican Americans and Puerto Ricans, although the results were attenuated for Puerto Ricans after adjustment for individual-level covariates.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have reported associations between higher Latino ethnic density and lower levels of depression overall 1718 or among only men, 89 and a curvilinear association between Latino ethnic density and depression, with those living in areas of moderate ethnic density having the most depressive symptoms. 19 In the only study to evaluate the association between residential segregation and mental health among Latinos, Lee 20 evaluated residential segregation as measured by the isolation index among 400 Latinos in the Midlife Development in the US (MIDUS) study in Chicago. Lee found that residential segregation was associated with a greater number of depressive and anxiety symptoms among both Mexican Americans and Puerto Ricans, although the results were attenuated for Puerto Ricans after adjustment for individual-level covariates.…”
Section: Introductionmentioning
confidence: 99%